BATING A REFERENCE INSTALLATION BASED ON CONTROLLED-POTENTIAL COULOMETRY METOD IN THE FRAME OF IMPROVING THE STATE PRIMARY STANDARD GET 176 AND ITS MEASUREMENT CAPABILITIES - V. M. Zyskin; A. Iu. Shimolin; A. V. Sobina; G. I. Terentiev (Стандартные образцы)
The results of developing of reference installation, based on a controlled-potential coulometry, in the frame of improving the State primary standard of the units of mass (molar) fraction and mass (molar) concentration of a component in the liquid and solid substances and materials GET 176 are presented. The physical principles of controlled-potential coulometry, content and metrological characteristics of the developed installation are considered. Measurement results of copper, iron and lead contents in the certified reference materials of metals' solutions and CRM of brass produced by BAM, Germany, obtained using reference installation are given.